The Effect of Aggregate-Forming Minerals on Thermodynamic Parameters Using Surface Free Energy Concept and Its Relationship with the Moisture Susceptibility of Asphalt Mixtures - Gholam Hossein Hamedi; Mohammad Reza Esmaeeli; Vahid Najafi Moghaddam Gilani; Seyed Mohsen Hosseinian (Advances in Civil Engineering)
Moisture damage is known to be a key factor influencing the durability of asphalt pavements. This phenomenon will reduce the mechanical properties of asphalt mixtures due to its destructive effects on the adhesion of the bitumen-aggregate system and the cohesion of the bitumen membrane. The mineral properties of the aggregates of asphalt mixtures are one of the factors affecting moisture susceptibility. Therefore, the surface free energy (SFE) method, as one of the thermodynamic methods, and indirect tensile strength test (ITST) have been used to determine the failure mechanism and the rate of change of adhesion properties of asphalt mixtures under the influence of mineralogical characteristics. Prior to the above tests, an X-ray fluorescence spectrometry (XRF) test was performed to identify aggregate-forming minerals in eight different types of aggregates with various minerals from eight mines, and also the apparent bitumen film thickness was measured. XRF test results showed that most parts of the aggregates in mines 1– 6 were composed of SiO2, which had strong acidic properties, according to the SFE results. ITST results showed that samples constructed with aggregates of mine 7 and 8 (with high CaO mineral content) experienced a higher TSR than other mixtures in all freeze-thaw (F-T) cycles. Results of the SFE method showed that aggregates with more calcareous properties had a smaller acidic component and a larger basic component. In mines 7 and 8, where the nonpolar component of their aggregates was larger, the tendency of the aggregates to adherence and wettability by water decreased. The adhesion free energy (AFE) between bitumen and aggregates with higher CaO and less SiO2 amounts was more than AFE between bitumen and aggregates with lower CaO and higher SiO2 amounts, in dry conditions. The presence of higher amounts of CaO in aggregates increased AFE of bitumen-aggregate in presence of water from a negative value to zero. In linear regression analysis, due to the positive regression coefficient of the CaO mineral, this mineral had a positive impact on TSR; on the other hand, due to the negative regression coefficient of the SiO2 mineral, this mineral had a negative impact on the TSR of asphalt mixtures.